Gestión municipal y sistemas administrativos de la Municipalidad Provincial de Loreto-Nauta - Gomez Mondragón, María Luisa (2023)
The present investigation entitled: MUNICIPAL MANAGEMENT AND ADMINISTRATIVE SYSTEMS OF THE PROVINCIAL MUNICIPALITY OF LORETO-NAUTA, had as its general objective: To determine the relationship between municipal management and administrative systems of the Provincial Municipality of Loreto-Nauta period 2021-2022. The type of research was descriptive, with a non-experimental design and it was carried out with a sample of 32 collaborators from the Municipality. Coming to the conclusion that there is a relationship between both variables, so it is important that they work together and thus develop properly in order to achieve the goals of the Municipality under study.